Islamic finance education: Current state and challenges for Pakistan - Minhas Akbar; Ahsan Akbar; Hafiz Sajid Yaqoob; Ammar Hussain; Libuše Svobodová; Fakhra Yasmin (Cogent Economics & Finance, 2023)
Islam stipulates its adherents to abide by religious principles in their economic transactions. The aim of this study is twofold. First, it accounts for the adherence of Shariah board members of Islamic banks with the Fit and Proper Criteria (FAPC) promulgated by State Bank of Pakistan (SBP). Second, it explores the current state of provision of Islamic finance education in the universities and madaris (i.e., Islamic seminaries) in Pakistan. This is the unique study in a sense because it draws attention of the stakeholders concerned (i.e., SBP, Higher Education Commission, Ittehad-e-Tanzimat Madaris-e-Deeniya & Ministry of Education) to revisit and make strategic milestones in congruent with the demand-supply gap of Islamic professional experts. Total sample consists of 21 banks, out of which the first five are full-fledged Islamic and remaining 16 are the commercial banks with Islamic banking branches. Descriptive research design has been employed to examine the supply of Shariah experts from madaris and universities in Pakistan. Our findings reveal the following: (1) Profiles of all the Shariah board members fully comply with the FAPC of SBP, and more than 50% of members represent multiple boards of Islamic banks. (2) With 26,000 madaris across Pakistan, 75% of the Shariah experts received their education from one Madrisa named Jamia-dar-ul-uloom, Karachi. Notably, province-wise stats highlight Punjab atop in terms of madaris (45% to 56%) in the country, though it produces less than 10% scholars for the Islamic banks' Shariah boards. A similar situation persists in Khyber Pakhtunkhwa that has 1354 to 3136 madaris and only one Shariah scholar received education from this province. Karachi, the capital of Sindh province and hub of Islamic seminaries, solely contributed more than 85% SB members to the Islamic banks. (3) Among the top fifteen business schools of Pakistan, only four are offering a degree in Islamic finance. Moreover, these four schools have only eight full-time faculty members with a core degree in Islamic finance. This study suggests the practitioners to increase the supply of Shariah scholars and also strengthen the capabilities and skills of human capital regarding Islamic finance education through education, training, social awareness and capacity building.
Keywords: 330; banking and financial system; Islamic finance education; madrasa; Pakistan; Shariah board members; University